2017
DOI: 10.1007/s00125-017-4349-5
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and ageing: improving ageing outcomes beyond glycaemic control

Abstract: In a world where the population is ageing, there is growing interest and demand for research evaluating strategies that address the ageing process. After 60 years of successful use of metformin in our pharmaceutical armamentarium, we are learning that, beyond improving glycaemic control, metformin may have additional mechanisms and pathways of action that need further study. Although, metformin’s effect on clinical ageing outcomes may still be considered speculative, the findings from studies into cellular and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
97
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 66 publications
1
97
0
2
Order By: Relevance
“…Moreover, metformin mediates histone modification and epigenetic regulation via reducing the activities of DNA acetyltransferases and methylases . Metformin also plays a major role in the prevention of ageing and ageing‐related disorders such as cancer, cardiovascular diseases, osteoporosis, and neurocognitive diseases . Studies have shown that metformin specifically influences the lifespan by activating AMPK, as an inhibitor of NF‐kB.…”
Section: Effects Of Metformin On Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, metformin mediates histone modification and epigenetic regulation via reducing the activities of DNA acetyltransferases and methylases . Metformin also plays a major role in the prevention of ageing and ageing‐related disorders such as cancer, cardiovascular diseases, osteoporosis, and neurocognitive diseases . Studies have shown that metformin specifically influences the lifespan by activating AMPK, as an inhibitor of NF‐kB.…”
Section: Effects Of Metformin On Ageingmentioning
confidence: 99%
“…52 Metformin also plays a major role in the prevention of ageing and ageing-related disorders such as cancer, cardiovascular diseases, osteoporosis, and neurocognitive diseases. 54,55 Studies have shown that metformin specifically influences the lifespan by activating AMPK, as an inhibitor of NF-kB. Similarly, Moiseeva et al 56 assert that metformin prevented the translocation of NF-kB to the nucleus and inhibited the phosphorylation of IkB and IKKα/β in senescent cells.…”
Section: Effec Ts Of Me Tformin On Ag Eingmentioning
confidence: 99%
“…In their review, Valencia et al [29] outline potential mechanisms by which metformin interferes with the ageing process, independent of blood glucose regulation. For example, the effects of metformin on inflammation and reactive oxygen species are thought to reduce DNA damage, whilst its effects on ceramides (which contribute to reduced myoblast numbers in the elderly) may also help to improve tissue health and function.…”
mentioning
confidence: 99%
“…Metformin is a highly effective treatment that is associated with weight loss and probable cardioprotection, and it is being investigated for its potentially beneficial effects on cancer risk and outcomes 18 and aging. 19 It should be noted, however, that metformin also causes quite considerable gastrointestinal (GI) side effects in ~ 10% of individuals who are prescribed the drug, leading to cessation in ~ 5%. The mechanisms for GI intolerance are also poorly understood.…”
Section: Metformin Efficacymentioning
confidence: 99%